Detecting entanglement structure in continuous many-body quantum systems - Kunkel, Philipp; Prüfer, Maximilian; Lannig, Stefan; Strohmaier, Robin; Gärttner, Martin; Strobel, Helmut; Oberthaler, Markus K. (Physical review letters, 2022)
A prerequisite for the comprehensive understanding of many-body quantum systems is a characterization in terms of their entanglement structure. The experimental detection of entanglement in spatially extended many-body systems describable by quantum fields still presents a major challenge. We develop a general scheme for certifying entanglement and demonstrate it by revealing entanglement between distinct subsystems of a spinor Bose-Einstein condensate. Our scheme builds on the spatially resolved simultaneous detection of the quantum field in two conjugate observables which allows the experimental confirmation of quantum correlations between local as well as nonlocal partitions of the system. The detection of squeezing in Bogoliubov modes in a multimode setting illustrates its potential to boost the capabilities of quantum simulations to study entanglement in spatially extended many-body systems.
Gesehen am 09.02.2022